Residency of bull sharks, Carcharhinus leucas (Carcharhiniformes: Carcharhinidae), at San Pedrillo Islet in Islas Murciélago, North Pacific of Costa Rica - López-Garro, Andrés (2021)
Introduction: The bull shark, Carcharhinus leucas, is particularly vulnerable to anthropogenic actions because of its permanence in coastal ecosystems; populations depletion is registered in different places around the world. Aggregations of bull sharks have been reported in the North Pacific of Costa Rica, at Islas Murciélago, within the Guanacaste Conservation Area. Objective: To study the residency of bull sharks at San Pedrillo islet, Islas Murciélago. Methods: During the study period (June 2013 to February 2015) we used passive telemetry to tag 10 bull sharks. Results: All the sharks tagged were females, they were detected on 59 798 occasions by the acoustic receiver deployed in San Pedrillo. Acoustic signals from tagged sharks were received for a total period of 1 to 229 days (mean = 73.9 ± 71.3 days), with the last detections occurring on 9 January 2015. The Residency Index for each tagged shark across the entire monitoring period ranged from 0.41 to 1.00. The bull shark activity showed a significant pattern throughout the day at the receiver that specifically corresponded with the daily light cycle. Conclusions: This study concludes that San Pedrillo is an aggregation site (cleaning station) for bull sharks (C. leucas), possibly related to reproduction and not feeding behaviors.